Commodity Transport Studies Coal - Planning Commission (Planning Commission, 1967)
Coal has been used as a source of energy since ancient times. However, it really became an important industrial fuel in the 19th century with the advent of the Industrial revolution. In fact, all important industry was coal-based till more sophisticated fuels and sources of energy were developed. Coal has played a vital role in the economy of India also and is likely to remain the most valuable fuel in our country for a long time to come. Apart from its use as a fuel, coal is also of great value as a raw material especially for the manufacture of various chemicals.
Joint Technical Group for Transport Planning, Planning Commission
Joint Technical Group for Transport Planning, Planning Commission